2010
DOI: 10.1016/j.physa.2010.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Return distributions in dog-flea model revisited

Abstract: A recent study of coherent noise model for the system size independent case provides an exact relation between the exponent $\tau$ of avalanche size distribution and the $q$ value of appropriate $q$-Gaussian that fits the return distribution of the model. This relation is applied to Ehrenfest's historical dog-flea model by treating the fluctuations around the thermal equilibrium as avalanches. We provide a clear numerical evidence that the relation between the exponent $\tau$ of fluctuation length distribution… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
(28 reference statements)
1
16
0
Order By: Relevance
“…(x) The distributions of returns in the Ehrenfest's dog-flea model exhibit a q-Gaussian form [118,119].…”
Section: Applicationsmentioning
confidence: 99%
“…(x) The distributions of returns in the Ehrenfest's dog-flea model exhibit a q-Gaussian form [118,119].…”
Section: Applicationsmentioning
confidence: 99%
“…Very recently, the probability distribution functions (PDFs) of the returns for this model have been investigated numerically by Pluchino et al 6 and fat-tailed distributions have been reported, which can be fitted by q-Gaussians. The physical quantity under investigation, the returns, is a commonly used one in areas such as turbulence, 7 finance, 8,9 DNA sequences, 10 and earthquake dynamics [11][12][13][14] in the literature. It is defined as…”
Section: Introductionmentioning
confidence: 99%
“…1 limit. 25,27,28 These findings suggest a new potential way for characterizing the presence of criticality. A remarkable feature is that such a behavior does not depend on the interval considered for the avalanche-size difference which have been shown in the inset.…”
Section: Spatial Behavior Of Neuron Release-probability Density Functionmentioning
confidence: 84%
“…If the system size is large enough, the cure will be overlapped and present the same parameter value of q. When the system size is large enough, the distribution of the returns can be fitted by a q-Gaussian given by 27,28 :…”
Section: Spatial Behavior Of Neuron Release-probability Density Functionmentioning
confidence: 99%